MERANCANG INTERNATIONAL ISLAMIC BOARDING SCHOOL DI JAKARTA BARAT DENGAN PENERAPAN ARSITEKTUR ISLAM - Andy Ismawan Arsyad; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
The Application of Islamic Architecture in the Design of the International Islamic Boarding School in West Jakarta can be interpreted as a place or building that serves to accommodate and serve the priority needs of Education for the West Jakarta area by applying the concept of Islamic Architecture where buildings, sites and education systems are made following the concept of Islamic Architecture. The design of the International Islamic Boarding School in West Jakarta is a place that functions as a place of education for learning for children, not only for general learning, but also for studying Islamic religion.